2019
DOI: 10.1002/cncr.32025
|View full text |Cite
|
Sign up to set email alerts
|

Validation of NRG oncology/RTOG‐0129 risk groups for HPV‐positive and HPV‐negative oropharyngeal squamous cell cancer: Implications for risk‐based therapeutic intensity trials

Abstract: Background Radiation Therapy Oncology Group (RTOG)‐0129 recursive partitioning analysis was the basis for risk‐based therapeutic intensification trials for oropharyngeal cancer (OPC). To the authors’ knowledge, the question of whether RTOG‐0129 overall survival (OS) estimates for low‐risk, intermediate‐risk, and high‐risk groups are similar in other data sets or applicable to progression‐free survival (PFS) is unknown. Therefore, the authors evaluated whether survival differences between RTOG‐0129 risk groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 29 publications
(63 reference statements)
1
59
1
Order By: Relevance
“…We previously showed that in Veterans with heavy tobacco exposure (a majority) 5,33 , survival for HPV+ and HPV− disease were in line with the rates reported by Ang et al for intermediate-risk and high-risk disease 5,34 . This effect was consistent across racial groups 35 , and matches long term results from both RTOG0129 and RTOG0522 11 . The introduction of immunomodulatory agents for OPSCC represents both an opportunity to improve clinical outcomes and a challenge in terms of stratifying patients to the appropriate treatment regimen and intensity [36][37][38][39][40] .…”
Section: Discussionsupporting
confidence: 79%
“…We previously showed that in Veterans with heavy tobacco exposure (a majority) 5,33 , survival for HPV+ and HPV− disease were in line with the rates reported by Ang et al for intermediate-risk and high-risk disease 5,34 . This effect was consistent across racial groups 35 , and matches long term results from both RTOG0129 and RTOG0522 11 . The introduction of immunomodulatory agents for OPSCC represents both an opportunity to improve clinical outcomes and a challenge in terms of stratifying patients to the appropriate treatment regimen and intensity [36][37][38][39][40] .…”
Section: Discussionsupporting
confidence: 79%
“…As excellent outcomes, in general, can be achieved in HPV‐positive HNSCC, the reasonable next step is to de‐intensify therapy, especially radiotherapy, to minimize treatment‐related toxicities and improve quality of life without compromising survival . One thing to be noticed is that the de‐intensification needs to happen carefully and only within the confines of a clinical trial.…”
Section: Biomarkers In Hnscc Tumor Tissuesmentioning
confidence: 99%
“…As early as 2000, the use of cisplatin or carboplatin in combination with radiotherapy has become a standard treatment approach for HNSCC . Several tissue biomarkers have shown a potential role in predicting response to platinum‐based therapy.…”
Section: Biomarkers In Hnscc Tumor Tissuesmentioning
confidence: 99%
See 2 more Smart Citations